The dark heart of Florence - Alexander, Tasha, 1969- (Alexander, Tasha, 1969- Lady Emily mystery., 2021)
"In the next Lady Emily Mystery The Dark Heart of Florence, critically acclaimed author Tasha Alexander transports readers to the legendary city of Florence, where Lady Emily and Colin must solve a murder with clues leading back to the time of the Medici. In 1903, tensions between Britain and Germany are starting to loom over Europe, something that has not gone unnoticed by Lady Emily and her husband, Colin Hargreaves. An agent of the Crown, Colin carries the weight of the Empire, but his focus is drawn to Italy by a series of burglaries at his daughter's palazzo in Florence--burglaries that might have international ramifications. He and Emily travel to Tuscany where, soon after their arrival, a stranger is thrown to his death from the roof onto the marble palazzo floor. Colin's trusted colleague and fellow agent, Darius Benton-Stone, arrives to assist Colin, who insists their mission must remain top secret. Finding herself excluded from the investigation, Emily secretly launches her own clandestine inquiry into the murder, aided by her spirited and witty friend, Cécile. They soon discover that the palazzo may contain a hidden treasure dating back to the days of the Medici and the violent reign of the fanatic monk, Savonarola--days that resonate in the troubled early twentieth century, an uneasy time full of intrigue, duplicity, and warring ideologies. Emily and Cécile race to untangle the cryptic clues leading them through the Renaissance city, but an unimagined danger follows closely behind. And when another violent death puts Emily directly in the path of a killer, there's much more than treasure at stake..."--